Clinical Applications of Fospropofol Disodium: Current Status, Advances, and Outlook - Shizhu Lin (Asploro Journal of Biomedical and Clinical Case Reports, 2026)
Fospropofol disodium (FD) is a water-soluble prodrug of propofol. Approved for marketing in China in 2021, it has become a new option for general anesthesia induction. Its key advantage lies in the fact that it does not require a lipid emulsion carrier, thereby avoiding traditional propofol-related adverse reactions such as lipid metabolism disorders and injection pain; at the same time, because the prodrug is slowly hydrolyzed by alkaline phosphatase to release active propofol, hemodynamic fluctuations are more gradual. However, the drug’s delayed onset of action (approximately 1-2 minutes slower than propofol), significantly higher incidence of paresthesia and pruritus, and ongoing safety concerns regarding formaldehyde metabolites constitute the main barriers to its clinical adoption. In recent years, with the launch of the Chinese version of FD (HX0507) and the conduct of multiple clinical studies, evidence supporting the use of FD in general anesthesia induction, ICU sedation, and comfort care has continued to accumulate. This article provides a systematic review of the pharmacological characteristics, clinical research evidence, and key unresolved issues regarding FD, aiming to serve as a reference for further research in the field of anesthesiology.